RASAL2 Plays Inconsistent Roles in Different Cancers - Zhou, Bolun; Zhu, Wei; Jiang, Xingjun; Ren, Caiping (Frontiers in Oncology, 2019)
RASAL2 belongs RAS GTPase-activating protein family and plays an important role in several cancers, including breast cancer, lung adenocarcinoma, pancreatic ductal adenocarcinoma and so on. Traditionally, RASAL2 was regarded as an inhibitor in cancers while recently some studies have found it is a promoter in some special types of cancers. In this issue, we have summarized the latest findings of RASAL2 in cancers, which may be important and useful in clinical practice. This review focuses on RASAL2 and RASAL2 plays interesting roles in different kinds of cancers, which is quite relevant to the topic of “Cancer Cell”. We evaluated the specific functions and mechanisms in different kinds of cancer cells. We concluded the functions and mechanisms of RASLA2 in inhibiting invasion, metastasis and angiogenesis and its opposite side, which may provide new ideas for cancer researches and treatments. RASAL2 often exhibits a relationship with clinical stage of cancers, histological grades, a poor prognosis and overall survival. Specifically, RASAL2 is a potential prognostic factor and a new therapeutic target for diagnosis and treatment. This review will be of great interest to oncologists and our review is systematical and updated.